2001
DOI: 10.1007/s004200000225
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cancer incidence among a population previously exposed to environmental cadmium

Abstract: These findings suggest that renal tubule dysfunction and a reduced glomerular filtration rate are predictors of mortality among persons previously exposed to environmental Cd. However, the results also suggest that overall mortality rates in Cd-polluted areas are not necessarily increased, because of the low mortality among those with no, or only slight, signs of low-molecular weight proteinuria. Overall cancer incidence may not be increased among residents in Cd-polluted areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 19 publications
3
46
2
1
Order By: Relevance
“…Kido et al (1988) and Iwata et al (1993) reported that the dysfunction of renal tubules after Cd exposure may become irreversible when β 2 -MG-U cr levels exceed 1,000 μ g / g cr. In a long run, an increase in mortality and reduction in life span was also observed among the residents with 1,000 μ g β 2 -MG / g cr in urine (Iwata et al 1991;Nishijo et al 1994;Arisawa et al 2001). Aoshima et al (1990Aoshima et al ( , 2000b proposed the same value of 1,000 μ g β 2 -MG / g cr as a screening level for renal dysfunction among Cd-exposed populations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Kido et al (1988) and Iwata et al (1993) reported that the dysfunction of renal tubules after Cd exposure may become irreversible when β 2 -MG-U cr levels exceed 1,000 μ g / g cr. In a long run, an increase in mortality and reduction in life span was also observed among the residents with 1,000 μ g β 2 -MG / g cr in urine (Iwata et al 1991;Nishijo et al 1994;Arisawa et al 2001). Aoshima et al (1990Aoshima et al ( , 2000b proposed the same value of 1,000 μ g β 2 -MG / g cr as a screening level for renal dysfunction among Cd-exposed populations.…”
Section: Discussionmentioning
confidence: 96%
“…Cases with discrepancy in intensity between exposure to Cd and response in terms of tubular dysfunction were observed also in the previous analysis (i.e., 17 cases out of 33 [51%] with Cd-U cr > 10 μ g / g cr; Ikeda et al 2003a), but it was even more so in the present analysis (51 cases out of 91 (56%); p < 0.10 by chi-squares test). The presence of these cases (e.g., Nakano et al 1985;Tohyama et al 1986;Aoshima 1987;Fan et al 1998;Arisawa et al 2001;Cai et al 2001) suggests that some subjects may be more resistant to Cd nephrotoxicity that others. Underlying mechanism certainly deserves further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many human epidemiological surveillance investigations have not identified a relationship between cadmium exposure and cancer risk, although experimental animal studies have clearly demonstrated an association. Therefore, although the International Agency for Research on Cancer (IARC) has classified cadmium as Carcinogenic (Group 1) in 1993, debate about this association has continued [49][50][51][52][53] .…”
Section: Toxicity and Disorders Caused By Cadmium Exposurementioning
confidence: 99%